Transient receptor potential (TRP) channels as a therapeutic target for intervention of respiratory effects and lethality from phosgene. (26th February 2016) - Andres, Devon; Keyser, Brian; Benton, Betty; Melber, Ashley; Olivera, Dorian; Holmes, Wesley; Paradiso, Danielle; Anderson, Dana; Ray, Radharaman
Highlights: Phosgene (CG) increases intracellular Ca 2+ ([Ca 2+ ] i ) in cultured BSMC and HPMEC. TRP channel inhibitors (general TRP, TRPV) prevent CG-induced [Ca 2+ ] i increase. TRP channel inhibitors protect mice against a 24-h lethal CG inhalation dose. TRP channels appear to play a role in CG toxicity both in vitro and in vivo . TRP channels are possible targets for intervention against CG toxicity. Abstract: Phosgene (CG), a toxic inhalation and industrial hazard, causes bronchoconstriction, vasoconstriction and associated pathological effects that could be life threatening. Ion channels of the transient receptor potential (TRP) family have been identified to act as specific chemosensory molecules in the respiratory tract in the detection, control of adaptive responses and initiation of detrimental signaling cascades upon exposure to various toxic inhalation hazards (TIH); their activation due to TIH exposure may result in broncho- and vasoconstriction. We studied changes in the regulation of intracellular free Ca 2+ concentration ([Ca 2+ ] i ) in cultures of human bronchial smooth muscle cells (BSMC) and human pulmonary microvascular endothelial cells (HPMEC) exposed to CG (16 ppm, 8 min), using an air/liquid interface exposure system. CG increased [Ca 2+ ] i ( p < 0.05) in both cell types, The CG-induced [Ca 2+ ] i was blocked ( p < 0.05) by two types of TRP channel blockers, SKF-96365, a general TRP channel blocker, and RR, a general TRPV (vanilloid type) blocker, in both BSMC and HPMEC. These effects correlate with the in vivo efficacies of these compounds to protect against lung injury and 24 h lethality from whole body CG inhalation exposure in mice (8–10 ppm × 20 min). Thus the TRP channel mechanism appears to be a potential target for intervention in CG toxicity.